Metamorphosis - Davies, Kyra-Aynsli (Rhodes University, 2026)
This thesis explores the manner in which fantasy literature resists and disrupts processes of differentiation, particularly those of colonial othering. The project focusses on The Soldier Son series, a trilogy of fictional novels by contemporary American author Robin Hobb, that can be considered ‘postcolonial fantasy’ due to its depiction of cultural imperialism and colonial discourse, and the magical doubling and metamorphosis of its protagonist, Nevare. Through a close reading of the trilogy, this project draws on a composite theoretical framework of fantasy, postcolonial, and psychoanalytic theory whose overlap with respect to the construction of difference and processes of othering, provides an opportunity to identify and explore the complex interplay between colonial discourse and internal processes of othering, expressed through and disrupted by Nevare’s psychic schism and the magical metamorphosis of his body. The Soldier Son trilogy further suggests the parallels between othering in colonial discourse and the internal othering of the protagonist Nevare through his psychic double, Soldier’s Boy. The concrete binaries and construction of difference upon which processes of othering rely are then blurred and disrupted through the fantastic in the text, specifically through the magical metamorphosis of the protagonist as the psychic schism between him and his alter ego begins to deteriorate. By examining both the doubling and the metamorphosis, the project aims to explore the subversive potential of fantasy literature to facilitate postcolonial critique. In this regard, the thesis utilises the works of notable postcolonial theorists including Edward Said and Homi Bhabha whose contemplation of the complex processes of othering and the construction of difference inherent to colonial discourse is supplemented by a consideration of the central role of the body herein. Utilising the theory of Judith Butler and other feminist theorists here, the body’s centrality to the othering process is further augmented by Rosemary Jackson’s analysis of the motifs of doubling, metamorphosis, and bodily disintegration in fantasy literature whose exploration of the links to Freudian psychoanalysis – particularly Freud’s writing on the uncanny and the developmental stages of the human ego – establishes its subversive potential.
examining cultural imperialism and the magical body in Robin Hobb’s The Soldier Son trilogy
Keywords: Fantasy fiction (http://id.loc.gov/authorities/subjects/sh85047114); Postcolonialism (http://id.loc.gov/authorities/subjects/sh97007835); Metamorphosis in literature (http://id.loc.gov/authorities/subjects/sh85084274); Hobb, Robin. Soldier son trilogy (http://id.loc.gov/authorities/names/n2005027995); Postcolonial literature (https://www.wikidata.org/wiki/Q1059134)